Aflatoxins B1 and B2 Contamination of Peanut and Peanut Products and Subsequent Microwave Detoxification - Mobeen, A.K.; Aftab, A.; Asif, A.; Zuzzer, A.S. (Journal of Pharmacy and Nutrition Sciences, 2022)
The effectiveness of microwave heating has been evaluated for the detoxification of aflatoxins contaminated peanut and peanut products. The products comprise of various confectionery such as peanut brittle toffee, peanut brittle slabs of sugar and jaggery, roasted and salted peanut and peanut butter which were highly contaminated with aflatoxins B1 ranging from 5 to 183µg/kg and aflatoxin B2 ranging from 7 to 46.7µg/kg. The level of aflatoxins was determined and subsequently products were treated to microwave heating, which resulted in the reduction of aflatoxins content. The microwave cooking resulted in 50 to 60 % reduction in the levels of aflatoxins B1, while B2 was reduced to non-detectable limits.